2018
DOI: 10.1177/2168479017716716
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapeutic Reports as Tools for Detecting Discrepancies in Continuity of Care

Abstract: A continuity program was implemented based on the drafting of a pharmacotherapeutic report, which allowed for detecting discrepancies and updating the patients' pharmacotherapeutic history, resulting in financial savings after its implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Cohen's kappa coefficient statistic for interrater reliability was 0.46 and 0.62 for the abstract and full-text screening, respectively [6]. Ten studies were ultimately included and are charted in Table 1 [7][8][9][10][11][12][13][14][15][16]. All studies were published in or after the year 2003 [7][8][9][10][11][12][13][14][15][16].…”
Section: Review Review Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Cohen's kappa coefficient statistic for interrater reliability was 0.46 and 0.62 for the abstract and full-text screening, respectively [6]. Ten studies were ultimately included and are charted in Table 1 [7][8][9][10][11][12][13][14][15][16]. All studies were published in or after the year 2003 [7][8][9][10][11][12][13][14][15][16].…”
Section: Review Review Methodsmentioning
confidence: 99%
“…Ten studies were ultimately included and are charted in Table 1 [7][8][9][10][11][12][13][14][15][16]. All studies were published in or after the year 2003 [7][8][9][10][11][12][13][14][15][16]. Over 80,000 patients living with COPD were represented across all 10 studies [7][8][9][10][11][12][13][14][15][16]; however, over 78,000 patients in this review were those identified in a population-based retrospective cohort of health administrative data in Ontario, Canada [13].…”
Section: Review Review Methodsmentioning
confidence: 99%
See 3 more Smart Citations